Superman action comics - Bendis, Brian Michael 1967- (DC Comics, 2019)
"The devastating repercussions from the Man of Steel graphic novel still reverberate as Metropolis enters a new age! The Daily Planet teeters on the brink of disaster! A new criminal element has made its way onto the streets of Superman's hometown!"--